enter image description here

I want to solve for $\angle BDC$, given $\angle ACB = 26^\circ$, $\angle ABC = 51^\circ$, $\angle BAD = 73^\circ$ and $CD$ bisects $\angle ACB$.

I have tried solving it using the fact that sum of inner angles of a triangle is $180^\circ$, but seems so strange that I cannot get the answer after an hour effort. Thank you for the help!

  • $\begingroup$ I don't know Chinese, but it seems like it says something about $BD$ as well $\endgroup$ – Andrei Nov 2 '18 at 4:52
  • $\begingroup$ @Andrei It just says "connect $BD$" $\endgroup$ – Edward Wang Nov 2 '18 at 4:53
  • 1
    $\begingroup$ Maybe applying the law of sines will help, but it seems like an ugly equation $\endgroup$ – Andrei Nov 2 '18 at 5:10

First, $\angle BAC=180^\circ-\angle ABC-\angle ACB=180^\circ-51^\circ-26^\circ=103^\circ$. Therefore, $$\angle CAD=\angle BAC-\angle BAD=103^\circ-73^\circ=30^\circ\,.$$ By the trigonometric form of Ceva's Theorem, $$\left(\frac{\sin(\angle CAD)}{\sin(\angle DAB)}\right)\,\left(\frac{\sin(\angle ABD)}{\sin(\angle DBC)}\right)\,\left(\frac{\sin(\angle BCD)}{\sin(\angle CDA)}\right)=1\,,$$ so $$\left(\frac{\sin(30^\circ)}{\sin(73^\circ)}\right)\,\left(\frac{\sin(x)}{\sin(51^\circ-x)}\right)\,\left(\frac{\sin(13^\circ)}{\sin(13^\circ)}\right)=1\,,$$ where $x:=\angle ABD$. This proves that $$\frac{\sin(x)}{\sin(51^\circ-x)}=\frac{\sin(73^\circ)}{\sin(30^\circ)}=2\,\sin(73^\circ)=2\,\cos(17^\circ)=\frac{\sin(34^\circ)}{\sin(17^\circ)}\,.$$ It follows that $$\frac{\sin(x)}{\sin(51^\circ-x)}=\frac{\sin(34^\circ)}{\sin(51^\circ-34^\circ)}\,.$$ Since $0\leq x\leq 51^\circ$, it is immediate that $x=34^\circ$. That is, $$\angle DBC=51^\circ-34^\circ=17^\circ$$ and $$\angle BDC=180^\circ-17^\circ-13^\circ=150^\circ\,.$$

In the proof above, we use the following lemma. To be precise, the step where we conclude $x=34^\circ$ follows from this lemma.

Lemma. If $\alpha$, $\beta$, and $\gamma$ are angles in $(0,\pi)$ such that $$\frac{\sin(\alpha-\beta)}{\sin(\beta)}=\frac{\sin(\alpha-\gamma)}{\sin(\gamma)}\,,$$ then $\beta=\gamma$.

We have $$\sin(\beta)\,\sin(\alpha-\gamma)=\sin(\gamma)\,\sin(\alpha-\beta)\,.$$ That is, $$\cos(\beta+\gamma-\alpha)-\cos(\alpha+\beta-\gamma)=\cos(\beta+\gamma-\alpha)-\cos(\alpha+\gamma-\beta)\,.$$ Consequently, $$\cos(\alpha+\beta-\gamma)=\cos(\alpha+\gamma-\beta)\,.$$ Hence, $$\alpha+\beta-\gamma=\pm(\alpha+\gamma-\beta)+2n\pi$$ for some integer $n$. That is, either $$\beta-\gamma=n\pi\text{ or }\alpha=n\pi$$ for some integer $n$, but since $0<\alpha<\pi$, we conclude that $$\beta-\gamma=n\pi$$ for some integer $n$. Because $-\pi<\beta-\gamma<+\pi$, we must have $$\beta=\gamma\,.$$ (However, without the restriction that $\alpha,\beta,\gamma\in(0,\pi)$, we can only conclude that either $\alpha$ or $\beta-\gamma$ is an integer multiple of $\pi$.)

  • 1
    $\begingroup$ $180 - 51 - 26 = 103$. That would give a better answer. $\endgroup$ – Quang Hoang Nov 2 '18 at 5:35
  • $\begingroup$ @QuangHoang Ach so! Thanks! $\endgroup$ – Batominovski Nov 2 '18 at 5:37
  • 1
    $\begingroup$ For the lemma you could also show that $\dfrac{\sin (\alpha-x)}{\sin x}$ is monotonic in that interval $\endgroup$ – Hari Shankar Nov 2 '18 at 6:03

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.